(untitled) (Journal of Business Management and Accounting, 2018)
Zakah has been a national affair among Muslim countries such that each country manages its own collection and distribution. However, there has been an effort to internationalize zakah management since 2009 when the idea of the World Zakat Fund was suggested by the Malaysian government. This is an important innovation as the Prophet (PBUH) emphasized that Muslims all over the world are one and brothers to one another. Since the idea started in 2009, the subject of internationalization of zakah management is yet to receive adequate scholarly research attention. The present study fills this gap by discussing internationalization of zakah management and its advantages in poverty alleviation among Muslims. The study also gave other suggestions for improving zakah management in view of the complexity and extensive nature of poverty among Muslims in the 21st century.